Cross-sectional associations between exposure to per- and polyfluoroalkyl substances and body mass index among European teenagers in the HBM4EU aligned studies. (1st January 2023) - Schillemans, Tessa; Iszatt, Nina; Remy, Sylvie; Schoeters, Greet; Fernández, Mariana F.; D'Cruz, Shereen Cynthia; Desalegn, Anteneh; Haug, Line S.; Lignell, Sanna; Lindroos, Anna Karin; Fábelová, Lucia; Murinova, Lubica Palkovicova; et al.
Abstract: Per- and polyfluoroalkyl substances (PFAS) are widespread pollutants that may impact youth adiposity patterns. We investigated cross-sectional associations between PFAS and body mass index (BMI) in teenagers/adolescents across nine European countries within the Human Biomonitoring for Europe (HBM4EU) initiative. We used data from 1957 teenagers (12–18 yrs) that were part of the HBM4EU aligned studies, consisting of nine HBM studies (NEBII, Norway; Riksmaten Adolescents 2016–17, Sweden; PCB cohort (follow-up), Slovakia; SLO CRP, Slovenia; CROME, Greece; BEA, Spain; ESTEBAN, France; FLEHS IV, Belgium; GerES V-sub, Germany). Twelve PFAS were measured in blood, whilst weight and height were measured by field nurse/physician or self-reported in questionnaires. We assessed associations between PFAS and age- and sex-adjusted BMI z-scores using linear and logistic regression adjusted for potential confounders. Random-effects meta-analysis and mixed effects models were used to pool studies. We assessed mixture effects using molar sums of exposure biomarkers with toxicological/structural similarities and quantile g-computation. In all studies, the highest concentrations of PFAS were PFOS (medians ranging from 1.34 to 2.79 μg/L). There was a tendency for negative associations with BMI z-scores for all PFAS (except for PFHxS and PFHpS), which was borderline significant for the molar sum of [PFOA and PFNA] and significant for single PFOA [β-coefficient (95% CI) per interquartile range fold change = −0.06 (−0.17, 0.00) and −0.08 (−0.15, −0.01), respectively]. Mixture assessment indicated similar negative associations of the total mixture of [PFOA, PFNA, PFHxS and PFOS] with BMI z-score, but not all compounds showed associations in the same direction: whilst [PFOA, PFNA and PFOS] were negatively associated, [PFHxS] associated positively with BMI z-score. Our results indicated a tendency for associations of relatively low PFAS concentrations with lower BMI in European teenagers. More prospective research is needed to investigate this potential relationship and its implications for health later in life. Graphical abstract: Image 1 Highlights: Per- and polyfluoroalkyl substances (PFAS) may impact youth adiposity patterns. We used data from teenagers in nine European countries (HBM4EU initiative). PFOA associated cross-sectionally with lower body mass index (BMI) in teenagers. The mixture of [PFOA, PFNA, PFHxS and PFOS] associated with lower BMI. PFHxS had opposite effects from [PFOA, PFNA and PFOS].